Blood Loss and Transfusion Rates in Microsurgical Head and Neck Reconstruction. Issue 11 (November 2018) - Nguyen, Anson; Shin, Hope; Saint-Cyr, Michel; Verheyden, Charles
Abstract : Background: Free flap reconstruction cases of the head and neck are often complex, long and have a multitude of risks. One of the greatest risks is intraoperative blood loss and need for transfusion. The purpose of this study was to examine basic patient and procedure characteristics in head and neck free flap reconstruction pre- and postoperatively that may help to predict severity of blood loss. Methods: A retrospective chart analysis of 67 free flap reconstructions for head and neck defects was performed. Patient characteristics, surgical variables, length of stay, and postoperative complications were reviewed and compared between the transfused and nontransfused patients. Characteristics between transfused and nontransfused patients were analyzed using two-tailed t tests and Fisher's exact tests. Results: Of the 67 procedures, 19 reconstructions (28.4%) required a transfusion. Transfused patients were found to have a lower preoperative hemoglobin and elevated coagulation labs. The average length of stay was also statistically longer for transfused patients. There was no statistical difference in patient characteristics, length of surgery, type of free flap, or complication rate in the transfused versus nontransfused patients. Conclusions: Our study demonstrates that head and neck microsurgical resection and reconstruction presents patients with a transfusion risk of over 28%. We found that patients with a lower preoperative hemoglobin and abnormal coagulation levels are at a higher risk for receiving a transfusion. We also have demonstrated that patients who received a transfusion had a statistically significant longer length of stay.